Seismic response analysis of highway overcrossings including soil structure interaction. - Zhang, Jian
This paper presents a systematic procedure for the seismic response analysis of highway overcrossings. The study employs an elementary stick model and a more sophisticated finite element formulation to compute response quantities. All dynamic stiffnesses of approach embankments and pile groups are approximated with frequency independent springs and dashpots that have been established elsewhere. A real eigenvalue analysis confirms the one to one correspondence between modal characteristics obtained with the three dimensional finite element solutions and the result of the simpler stick model idealization. A complex eigenvalue analysis yields modal damping values in the first six modes of interest and shows that modal damping ratios assume values much higher than those used by Caltrans. The validity of the proposed method is examined by comparing the computed time response quantities with records from the Meloland Road and Painter Street overcrossings located in southern and northern California, respectively. The proposed procedure allows for inexpensive parametric analysis that examines the importance of considering soil structure interaction at the end abutments and centre bent. Results and recommendations presented by past investigations are revisited and integrated in comprehensive tables that improve our understanding of the dynamic characteristics and behaviour of freeway overcrossings. The study concludes with a step by step methodology that allows for simple, yet dependable dynamic analysis of freeway overcrossings, that involves a stick model and frequency independent strings and dashpots.
Keywords: Dynamic analysis; Highway bridges; Earthquakes; Soil structure interaction